Corona Virus Disease 2019 pandemic: Establishment of new or repurposed treatment centres to reduce the burden on the health system - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Al Ameen Medical College, 2020)
In the ongoing Corona Virus Disease-2019 (COVID-19) pandemic, due to the continuous rise in the number of cases, the health systems have been outstretched and they are finding it extremely difficult to respond to the rising caseload. From the global perspective, a total of 693224 cases ad 33106 deaths has been reported since the start of the outbreak in China [1]. It is worth noting that in a single day, 58411 cases have been reported worldwide, of which 54.3% cases were from the European region alone [1]. Moreover, the caseload and the pressure experienced by some of the European nations (like Italy, Spain, Germany, France, etc.) and the United States of America, all of which are developed nations, is not hidden from anyone of us [1].